Comparison of single CT scan assessment of bone mineral density, vascular calcification and fat mass with standard clinical measurements in renal transplant subjects: the ABC HeART study. Issue 1 (December 2015) - Kinsella, Sinead; Murphy, Kevin; Breen, Micheal; O'Neill, Siobhan; McLaughlin, Patrick; Coyle, Joe; Bogue, Conor; O'Neill, Fiona; Moore, Niamh; McGarrigle, AnneMarie; Molloy, Michael; Maher, Michael; et al.
Abstract Background Despite limitations of routine methods, Clinical Practice Guidelines support the assessment of bone mineral density (BMD) and vascular calcification in renal transplant recipients. Changes in fat mass also occur post-transplantation, although they are traditionally difficult to measure accurately. We report the feasibility, convenience and accuracy of measuring the above 3 parameters using a novel CT protocol. Methods We conducted a cross-sectional study of 64 first renal allograft recipients (eGFR > 30 ml/min/1.73 m2 ). Quantitative CT (QCT) BMD analysis was conducted using CT lumbar spine (GE Medical Systems Lightspeed VCT & Mindways QCT Pro Bone Mineral Densitometry System Version 4.2.3) to calculate spinal volumetric BMD and compared with standard DXA calculated areal BMD at the spine, hip and distal forearm. Abdominal aortic calcification was assessed by semi-quantitative Aortic Calcification Index (ACI) method and compared with lateral lumbar x-ray Kappuila score and pulse wave velocity (PWV). Visceral and subcutaneous adipose tissue volume (Osirix 16 Ver 3.7.1) was compared with BMI. Results Participants were 61 % male, had a mean age of 47 years, median ESKD duration of 5.4 years and a mean eGFR of 54 ml/min. iDXA median T-score at proximal femur was −1.2 and at lumbar spine was −0.2. Median QCT Trabecular T-score at lumbar spine was −1.2. The percent of subjects with a T-score of <2.5 by site and method was DXA Proximal Femur: 7 %, DXA distal radius: 17 %, DXA spine: 9 %, QCT (American College of Radiology cutoffs): 9 %. CT derived ACI correlated with PWV (r  = 0.29, p  = 0.02), pulse wave pressure (r  = 0.51, p  < 0.001), QCT Trabecular (−0.31, p  = 0.01) and cortical volumetric BMD and history of cardiovascular events (Mann–Whitney U, p  = 0.02). Both visceral and subcutaneous adipose tissue correlated with BMI (r  = 0.63 & 0.64, p  < 0.001). Conclusions Single CT scan triple assessment of BMD, vascular calcification and body composition is an efficient, accurate and convenient method of risk factor monitoring post renal transplantation.